African Union Great Green Wall Initiative Strategy and Ten-Year Implementation Framework (2024-2034): Summaries of the Four Strategic Intervention Axes - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
These briefs present the four Strategic Intervention Axes of the revised African Union Great Green Wall (GGW) Initiative Strategy and Ten-Year Implementation Framework (2024–2034). The Axes are designed to drive progress toward the GGW’s vision and objectives by providing a coherent structure for coordinated action. They include: